Phylogeny-based species delimitation of southern Philippines bent-toed geckos and a new species of Cyrtodactylus (Squamata: Gekkonidae) from western Mindanao and the Sulu Archipelago - Welton, Luke J.; Siler, Cameron D.; Diesmos, Arvin C.; Brown, Rafe M. (Zootaxa, 2010)
Using a combination of fixed morphological character differences, mitochondrial DNA sequence data, and an estimate of phylogeny as our guide, we describe a new species of bent-toed gekkonid lizard (Genus: Cyrtodactylus) from southwestern Mindanao Island, and northeastern portions of the Sulu Archipelago, southern Philippines. The new species resembles C. annulatus, but differs from this and all other congeners by characteristics of external morphology, color pattern, and body size. In addition, the new species is distinguished from congeners by marked genetic divergence and reciprocal monophyly of mitochondrial DNA sequences. The new species is common in pristine, low elevation gallery forests throughout Pasonanca Natural Park, Zamboanga Peninsula, southwestern Mindanao Island, and the northeastern portions of the Sulu Archipelago.